BODILY OPPRESSION AND INTERACTION: A SPATIAL ANALYSIS ON MRS. DALLOWAY - Tingting Li (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
Virginia Woolf is one of the most influential novelists in British literature and also one of the pioneers who leads the trend of literary modernism. Just as artists engaged in Cubic painting and sculpture in the same developmental period, such modern novelists as Virginia Woolf were keenly aware of the significant influence of space on their artistic creation. Therefore, this essay tries to explore the interrelation between men and space through analyzing Woolf’s modernist masterpiece—Mrs. Dalloway. Focusing on Clarissa Dalloway and Septimus Warren Smith, this essay aims to interpret how they struggle against bodily oppressions, namely the restraints and controls imposed on the individual body by the external space, and how they make an effort to interact with space as a way out. Clarissa’s interaction with space involves her participation in constructing urban space through walking, directly affecting the external space; at the same time, urban space also affects her internal space by cheering her up when she walks in the city. And as for Septimus, he integrates into space by committing suicide so that his flesh is eventually decomposed to dust and returns to nature. By analyzing all those, this essay tries to argue that modern society not only makes people suffer from spatial oppression but also offers new opportunities and development prospects, enabling people to liberate themselves from numerous oppressions and create positive integration and communication with their surrounding space, which finally reaches a balanced state.